2022
DOI: 10.1002/term.3325
|View full text |Cite
|
Sign up to set email alerts
|

Integrating nonlinear analysis and machine learning for human induced pluripotent stem cell‐based drug cardiotoxicity testing

Abstract: Utilizing recent advances in human induced pluripotent stem cell (hiPSC) technology, nonlinear analysis and machine learning we can create novel tools to evaluate drug-induced cardiotoxicity on human cardiomyocytes. With cardiovascular disease remaining the leading cause of death globally it has become imperative to create effective and modern tools to test the efficacy and toxicity of drugs to combat heart disease. The calcium transient signals recorded from hiPSC-derived cardiomyocytes (hiPSC-CMs) are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Results showed that the neural network outperformed the other two models with an initial accuracy of 71.4% in drug classification, which was boosted to 80% accuracy with the addition of data preprocessing steps. In addition, t‐SNE, a dimensionality reduction technique, was used to visualize how data preprocessing can help the separation of drug effects and allow ML algorithms to detect subtle variations among different drugs 61 . In another study, the t‐SNE algorithm was used to investigate the structure–function relationships of cardiac organoids generated from different micropattern sizes.…”
Section: Integration Of Ai Workflow With Organoid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the neural network outperformed the other two models with an initial accuracy of 71.4% in drug classification, which was boosted to 80% accuracy with the addition of data preprocessing steps. In addition, t‐SNE, a dimensionality reduction technique, was used to visualize how data preprocessing can help the separation of drug effects and allow ML algorithms to detect subtle variations among different drugs 61 . In another study, the t‐SNE algorithm was used to investigate the structure–function relationships of cardiac organoids generated from different micropattern sizes.…”
Section: Integration Of Ai Workflow With Organoid Systemsmentioning
confidence: 99%
“…In addition, t-SNE, a dimensionality reduction technique, was used to visualize how data preprocessing can help the separation of drug effects and allow ML algorithms to detect subtle variations among different drugs. 61 In another study, the t-SNE algorithm was used to investigate the structure-function relationships of cardiac organoids generated from different micropattern sizes. This data visualization technique allowed us to identify the correlation between pattern size and parametric functional parameters of cardiac organoids, revealing important associations.…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…In our literature review, we specifically targeted research articles that employ ML models to enhance the comprehension of hiPSC-CM behavior. We deliberately excluded studies that integrate ML into the use of hiPSC-CMs as models, like drug cardiotoxicity or disease progression (Heylman et al, 2015;Lee et al, 2017;Maddah et al, 2020;Grafton et al, 2021;Juhola et al, 2021;Kowalczewski et al, 2022;Yang et al, 2023). To assemble the cohort of research papers, a comprehensive literature search was conducted using the PubMed-NCBI database with the following search terms: Other searches with relevant key terms yielded no results; therefore, they were omitted from this list.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…However, its application to toxicological screening systems as a replacement for in vitro and in vivo tests remains challenging. Kowalczewski et al 15 reported that a machine-learning model can distinguish the responses of hiPSC-derived cardiomyocytes to representative arrhythmogenic agents, isoproterenol, verapamil, and cisapride, based on known calcium wave parameters. Monzel et al 16 developed a machine-learning model that can discriminate between dopaminergic neuron-specific toxin 6-hydroxydopamine-treated hiPSC-derived neuronal organoids.…”
Section: Introductionmentioning
confidence: 99%